Effect of ethanol on ketone metabolism - Lefèvre, André (1970)
Ketonuria has been observed in alcoholics. To study the mechanism of this effect, healthy, volunteers were given adequate diets (36% of calories as lipid and 15% as protein) for 18 days, with isocaloric replacement of carbohydrate (46% of calories) by either ethanol or additional fat. The latter resulted in a high fat diet, with 82% of calories as lipid. After about 1 wk of alcohol, massive and persistent ketonuria developed. Compared with the control period, there was a 30-fold increase in fasting blood acetoacetate and β-hydroxybutyrate (P < 0.001). With the high fat diet, acetoacetate and β-hydroxybutyrate increased 8- to 10-fold (P < 0.001). In the postprandial state, ethanol also induced hyperketonemia, but less markedly than when ethanol followed an overnight fast. With low fat diets (5% of calories), alcohol (46% of total calories) did not induce ketonuria or hyperketonemia, suggesting that a combination of alcohol and dietary fat is necessary. The addition of alcohol to rat liver slices did not affect ketogenesis. In rats pretreated with alcohol for 3 days, however, ketonemia developed, hepatic glycogen was decreased, and liver slices (incubated with palmitate-(14)C and glucose) had a significant increase in acetoacetate production, when compared to carbohydrate pretreated controls. Alcohol pretreatment or addition of alcohol in vitro had no effect on acetoacetate utilization by rat diaphragms, and decreased only slightly the conversion of β-hydroxybutyrate-(14)C to (14)CO(2). Thus, the hyperketonemia and ketonuria observed after alcohol consumption cannot be attributed to an immediate effect of alcohol, but is the consequence of a delayed change in intermediary metabolism characterized by increased hepatic ketone production from fatty acids, possibly linked to ethanol-induced glycogen depletion and depression of citric acid cycle activity.